2004
DOI: 10.1007/bf02931535
|View full text |Cite
|
Sign up to set email alerts
|

The yeast flora of some decaying mushrooms on trunks of living trees

Abstract: ABSTRACT. Several ascomycetous and basidiomycetous yeasts were isolated from rotten mushrooms on the trunks of beech and tamarisk trees. One strain, identified as the novel species Cryptococcus allantoinivorans, assimilated allantoin as the sole carbon source. Phylogenetically it belongs to the C. laurentii complex, Papiliotrema bandonii being the closest relative. Some ascomycetous strains could not be distinguished from Pichia guillermondii, but deviated considerably in rDNA sequences. In addition to these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…Sequence analysis showed that the strains exhibit identical D1/D2 26S rRNA gene domains and similar 5.8S-ITS regions to a yeast strain isolated from a decaying mushroom (Middelhoven, 2004), which was recently described as C. cretensis (Middelhoven & Kurtzman, 2007). This high similarity was also confirmed by sequence analysis of the actin gene, indicating that they belong to the same yeast species.…”
Section: Discussionsupporting
confidence: 60%
“…Sequence analysis showed that the strains exhibit identical D1/D2 26S rRNA gene domains and similar 5.8S-ITS regions to a yeast strain isolated from a decaying mushroom (Middelhoven, 2004), which was recently described as C. cretensis (Middelhoven & Kurtzman, 2007). This high similarity was also confirmed by sequence analysis of the actin gene, indicating that they belong to the same yeast species.…”
Section: Discussionsupporting
confidence: 60%
“…Maire growing on a Tamarix tree near the sea side in Plakias, Crete, Greece in October 2000 (Middelhoven 2004). The type strain is preserved as a lyophilized preparation in two culture collections, viz.…”
Section: Origin and Depositsmentioning
confidence: 99%
“…: Fr.) Pers., growing on a beech tree, Fagus sylvatica L., in Wageningen, The Netherlands, in September 2000 (Middelhoven 2004). The type strain was deposited in two culture collections, viz.…”
Section: Origin and Depositsmentioning
confidence: 99%
See 1 more Smart Citation
“…Araştırmaya konu olan ılgın ağaçlarında, türler arasında farklılıklar olmakla birlikte, flavonoidlerin, fenolik yapılı bileşiklerin, kumarinlerin, taninlerin ve serbest alkollerin yoğun bulunabildiği rapor edilmiştir (13) . Farklı yapıla-rında antiseptik özelliği bulunmasına karşılık, bazı basidiyomiçet ve askomiçet mantarlar ılgın ağaçlarında çoğalabilmektedir (26) .…”
Section: Discussionunclassified